Decision making in entrepreneurial finance: A behavioral perspective - Rassoul Yazdipour (The Journal of Entrepreneurial Finance and Business Ventures, 2009)
Central questions in entrepreneurship and entrepreneurial finance are briefly discussed and case is made for the need for applying the behavioral finance theories and models to better understand the decision making dynamics that is involved at each stage of the entrepreneurial process. By dissecting a venture's total risk into a Resident Risk component and a Behavioral Risk component, attempt is made in this writing to introduce a preliminary risk model for evaluating key entrepreneurial decisions like the decision to launch and fund a new venture. Although the focus here is on individual decision making under highly uncertain entrepreneurial environments, but the suggested risk framework and the related discussions can be extended to decision making processes in all other uncertain environment.
Keywords: 650